2013
DOI: 10.1111/jdv.12347
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous melanoma in patients treated with tumour necrosis factor inhibitors: a retrospective series of 15 patients

Abstract: Our case series does not reveal a distinct profile of melanoma in the patients exposed to TNF inhibitors. Additional prospective trials including larger number of patient are needed to demonstrate the possible link between biological therapy with TNF inhibitors and development of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In addition, one must also consider the recent suggestion of a paradoxical protective role of sun exposure [14,15]. It has been postulated that chronic anti-TNF treatment, affecting immune surveillance and collateral interferon inhibition could impair defenses against melanoma cell proliferation [2,6]. Surprisingly, melanoma reports are few with respect to anti-TNF drugs worldwide [2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, one must also consider the recent suggestion of a paradoxical protective role of sun exposure [14,15]. It has been postulated that chronic anti-TNF treatment, affecting immune surveillance and collateral interferon inhibition could impair defenses against melanoma cell proliferation [2,6]. Surprisingly, melanoma reports are few with respect to anti-TNF drugs worldwide [2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that chronic anti-TNF treatment, affecting immune surveillance and collateral interferon inhibition could impair defenses against melanoma cell proliferation [2,6]. Surprisingly, melanoma reports are few with respect to anti-TNF drugs worldwide [2][3][4][5][6][7][8][9]. A French study suggests that a critical point is observation timing; 47.6 months is the mean period from beginning treatment to melanoma occurrence in their experience [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Special consideration should be reserved to melanoma, as concern about the possible occurrence of primary lesions, as well as more aggressive course and activation of dormant lesions are controversial issues [22,23,37]. Two recent studies reported a significant degree of association, confirming the need for further studies in order to establish the actual existence of a risk [36,38].…”
Section: Other Malignanciesmentioning
confidence: 99%
“…More rarely, lupus erythematosus [24,25], acneiform eruption [26], sarcoidosis [27], anular granuloma [28], interstitial granulomatous dermatitis [29], lichenoid eruptions [30], erythema multiforme [31], leucocytoclasic vasculitis [32], purpura [33], dermatomyositis [34], eruptive benign lesions [35], and melanoma [36][37][38] are reported. In the present paper, we have focused on cutaneous adverse reactions to anti-TNFα agents and their proper management, comparing our data and results with those reported in the international literature.…”
Section: Introductionmentioning
confidence: 99%